Investigating Junior High School Student in Learning Reading Through Word Search Puzzle Game : Case Study - Ripaldi, Diki; Pujiawati, Nia; Al-Baekani, Abdul Kodir (IKIP Siliwangi, 2025)
Many students struggle to form simple sentences for everyday conversations. Vocabulary is the main foundation of language, and the richness of a person's understanding greatly determines their ability to capture meaning, understand context, and connect ideas in a text. Teachers must pay special attention to gain students' motivation to expand their vocabulary. Therefore, the research aimed to explore the implementation and investigate students in word-search puzzle games as a learning medium to assist students in reading classrooms. The researcher used qualitative research with a case study design. Five students of junior high school students were involved in this research. Research data was collected through interviews and observation. The data was analyzed by thematic analysis. The study found that teachers implementing a learning strategy following the theory of Safadi and Rababah encourage student engagement and improve reading skills by using the Word Search Puzzle Game as a learning medium. There are four stages to implementing this strategy. This strategy can encourage students to learn so that they can explore their reading skills. It can be concluded that integrating the Word Search Puzzle Game into reading learning can increase students' cognitive, affective, and behavioral engagement and prove that interactive and exciting learning media can help achieve learning.